Controller design for tidal energy systems - Wang, Shengxiao (2014)
The report reviews the mathematical modulation of tidal turbine drive chain, Permanent Magnet Synchronous Generator (PMSG) as well as some of the control methods. Research papers in this PMSG controller design have also been reviewed and it shows that there is still room for improvement in current controller designs. In this project, the author has implemented tidal turbine and PMSG in Matlab Simulink, many control methods such as Proportional-Integral control, decoupling control and zero d-axis control has been introduced in the model as well. A preliminary study in reset control has also been carried out and a basic model of first-order-reset-element has been established. The simulation result of the system has much improvement compared to literatures reviewed.